Success and Failure Aspects of LMS in E-Learning Systems - Alhazmi, Abdulsalam; Imtiaz, Athar; Alhammadi, Fatima; Kaed, Ezzadeen (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Learning management systems (LMS) and their associated tools have created value for higher education institutions worldwide by improving content deliverability, accessibility, and retrievability. Nevertheless, many studies have criticised these systems for their teacher-centred approaches, which limit opportunities for social and informal learning. After several decades of institutions using LMS, this research aims to discuss the success and failure aspects of these LMS from various perspectives, including structure, content, and support for emerging technologies. Based on a thematic literature review and analysis, success and failure aspects are organised and verified by LMS experts. Alongside the aspects identified from the literature, these experts also noted several additional aspects of success and failure in LMS. The analysis results overall indicated the success aspects of LMS relate to seven key factors: single sign-on, learning management, content management, integration, security, tracking, and group management. Similarly, the failure aspects could be classified into eight factors: content creation and sharing, communicative features, structure, learning engagement, assessment, user interfaces, social and informal learning, and mobile features. The implications of the research for education institutions, instructors, developers, and system providers, as well as the resulting directions for future research, are thus also discussed to help increasing the chances of developing additional theoretical and practical insights.